Low cost carriers and tourism destinations development: case study of Oporto, Portugal - Costa, Vânia (2019)
Mobility is one of the characteristics of modern society. The world today, despite the uncertainties brought by globalization is an interconnected reality of networks, whether physical or virtual. In Europe this mobility is higher than before due to the new offer of routes and frequencies of airlines, mainly of the low cost carriers (LCC). Portugal is one of the countries that grew in terms of new routes, new destinations and above all new customers with economic impacts in the regions. Over the last decade, LCC at Oporto (OPO) airport have boosted their traffic volume by approximately 260%. The evolution of OPO airport, generated by LCC, has meant that other regional airports have followed this trend and have also experienced a positive and growing net impact on their local economy. The main issue of this study is to analyse the evolution of LCC air traffic at Francisco Sa Carneiro Airport in OPO and its economic impact on this airport's area of influence. We use a cost-benefit analysis model to determine the costs, benefits and net impact of low cost routes on the development of the local economy between 2005 and 2012. In 2005 these carriers started operating at OPO Airport.